(untitled) (African Journal of Biomedical Research, 2020)
The concept of dissecting human body revolutionized Anatomy as a sacred discipline. Evaluating sources of cadaver adds values to care of human remains with due respect to body donors for their magnanimous and selfless act in furtherance of medical education and research. This study aimed at bridging communication gap in getting the rightful cadavers for anatomic education with specific objectives addressing the challenges involved. The department’s Cadaver Registry contained: date and source of cadaver, gender, race, likely age, cause of death, autopsy report, type of embalmment, mode of release, financial expenditure and mode of disposal. Data were subjected to simple statistical analysis while Kendall’s Coefficient of Concordance was adopted for test of significance. Forty-one adult cadavers procured from five mortuaries were analysed with male to female ratio of 13 to 1 while student to cadaver ratio was 5 to 1. Unclaimed body dominated cause of death with 68.3% while the rest was armed-robbery. Autopsy was earlier performed on 9.8% of cadaver before acquisition. Undisclosed payment transpired on 80.5% before release from provincial mortuaries. Tests of significance amongst the characteristics were statistically-significant proven the itemized factors to be independent. Elucidative programmes were identified in checking the strong socio-cultural heritage against whole body bequeaths to acquire rightful cadavers. Main sources were from unclaimed body and legally executed criminals. Gender and student to cadaver ratios were promising for anatomic utilization. The proposed amendment on old anatomic act in Nigeria should be sagely incorporated with whole body bequeath affairs